FINANCIAL SECTOR STOCKS REACTION TO COVID-19 EVENTS - Peovski, Filip; Ivanovski, Igor; Ahmedi, Sulejman (Faculty of Economics - Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
Price fluctuations in the financial sector are often of major interest when projecting the general performance and state of the economy. The implications of the COVID-19 pandemic in the sector are analyzed through the event study method. A random sample portfolio of 20 financial sector stocks listed on the NYSE is used and its reaction on 15 different events throughout 2020 is observed. Results indicate that events in the earlier stage of the pandemic exhibit both higher abnormal returns and significance, compared to the ones at the latter stages, with a larger proportion of them being bad news. The financial sector is perceived to react significantly in such cases, usually anticipating them beforehand. As adjustment windows are rarely significant, the market’s reaction is deemed as efficient. The general conclusion is that the financial sector stocks react to important COVID-19 news, generating abnormal rather than expected returns.
Keywords: COVID-19; Efficient Market Hypothesis; Event study; financial sector, financial development, economic growth, real sector lending activity, resource allocation, macroeconomic environment, banking sector, non-bank financial institutions, capital markets.; stock market